Organizational and Economic Aspects of the Intellectual Transport Systems Effectiveness - A. O. Merenkov (Управление)
This article describes the intellectual transport systems (ITS) as a core to move to the «digital» economics of the 21st century. The research touched the approaches to understand of the ITS covered by both Russian and western scientists. The author defined basic parameters applicable for «digital» transport and logistics used by leading countries of the world. The article provides the author`s method estimate the level of forming the ITS projects having features to consider the customer requirements in quality of informational service. The special attention is also paid to parameters of organizational and economic nature. The research allowed to not only asses current developments of ITS projects in Russia but also to provide recommendations of ITS improvements. Studying the organizational parameters of ITS projects the author analyzed Japanese and the US experience in the area of building «digital» transport and logistics. The final part of article covers issues of training professionals in the ITS sphere for transportation complex of the 21st century. The study not only tells about scientific institutions in Russia, but points out the need to cooperate internationally in this filed